Anoxic biodesulfurization using biogas digestion slurry in biotrickling filters. (1st July 2019) - Zeng, Yong; Luo, Yiping; Huan, Chenchen; Shuai, Yiping; Liu, Yang; Xu, Lishan; Ji, Gaosheng; Yan, Zhiying
Abstract: In this study, an alternative technology for using chemically produced nitrate/nitrite as an electron acceptor for biogas anoxic desulfurization was developed. The method was validated through the investigation of the impacts of loading rate, trickling liquid velocity, empty bed residence time, liquid height/filler height ratio and restart on H2 S removal efficiency in biotrickling filters packed with polyurethane foam (BTF B) and multi-surface hollow spheres (BTF C). The results of this study showed that the best desulfurization efficiency was obtained at a liquid height/filler height ratio of 1/3, rather than at 1/2 or 1/6. In a 122-day experiment, the maximum elimination capacity of 81.29 gH2 S m −3 h −1 was achieved under a H2 S removal efficiency of 94.5%. In addition, the fastest restart process required only 8 days after 25 days of shutdown. High throughput sequencing results indicated that the microbial community structure was more stable below the liquid level than above the liquid level. The genus Sulfurimonas in BTF C was positively correlated with the loading rate (R 2 = 0.99, P < 0.01), but the significance of the correlation was lower in BTF B (R 2 = 0.76, P < 0.05). In general, the outcomes affirmed that utilizing biogas digestion slurry after nitrification (provided low-cost electron acceptor) could realize a stable and efficient desulfurization efficiency of biogas. Graphical abstract: Image 1 Highlights: Provide an economic scheme with bio-produced nitrate for biogas desulfurization. No introduction of exogenous pollutants and no emission of wastewater & gas. The liquid height/fillers height ratio of 1/3 could get a most stable H2 S removal. The fastest restart process only acquired 8 days after 25 d of shutdown.